1952
DOI: 10.1099/00221287-7-3-4-257
|View full text |Cite
|
Sign up to set email alerts
|

Conditions affecting the Growth of Bacterium coli on Bile Salts Media. Enumeration of this Organism in Polluted Waters

Abstract: SUMlClARY:The growth of Bacterium coli on agar media containing bile salts is conditioned by a number of factors. The proportion of total cells able to grow on a medium not containing bile salts rapidly declines at temperatures of incubation above 43". On a medium containing bile salts and lactose a distinctly inhibitory effect is observed at 37'; with most strains this effect is still more pronounced a t 4 4 ' . Some brands of bile salts are appreciably more inhibitory than others. Inclusion of phosphate in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1953
1953
1985
1985

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…These findings had suggested that normal nutrient broth contained substances which were inimical to the survival (or revival) of such damaged cells, though not to normal cells. In this connection Allen and his co-workers (Allen, Pasley & Pierce, 1952; Allen, Pierce t Smith, 1953; Childs & Allen, 1953) obtained higher counts of Escherichia coli and Streptococcus faecalis when cells from polluted water were resuscitated in nutrient broth prior to transfer to inhibitory selective media. These workers also showed that counts on bile salt media from suspensions of E .…”
mentioning
confidence: 98%
“…These findings had suggested that normal nutrient broth contained substances which were inimical to the survival (or revival) of such damaged cells, though not to normal cells. In this connection Allen and his co-workers (Allen, Pasley & Pierce, 1952; Allen, Pierce t Smith, 1953; Childs & Allen, 1953) obtained higher counts of Escherichia coli and Streptococcus faecalis when cells from polluted water were resuscitated in nutrient broth prior to transfer to inhibitory selective media. These workers also showed that counts on bile salt media from suspensions of E .…”
mentioning
confidence: 98%
“…incubating the impaired cells in a rich medium at room temperature for 5 2 h before plating out on, or enriching in, selective media (Allen et al 1952;Mossel & Ratto 1970). incubating the impaired cells in a rich medium at room temperature for 5 2 h before plating out on, or enriching in, selective media (Allen et al 1952;Mossel & Ratto 1970).…”
mentioning
confidence: 99%
“…In most instances these effects are so serious that populations released from such foods can only be inoculated into or onto selective media after a revitalization treatment known as resuscitation (Allen et al, 1952) has been carried out.…”
Section: Desiderata Of the Third Symposiummentioning
confidence: 99%